2018
DOI: 10.7812/tpp/17-152
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Pathway of Oral Cavity Cancer in an Integrated Health Care System

Abstract: Context: Survival for patients with oral cavity squamous cell carcinoma (OCSCC) has remained relatively stagnant despite advances in treatment. Few studies have examined why advanced-stage disease is diagnosed in 40% of patients with OCSCC nationally.Objective: To characterize the diagnostic pathway of OCSCC in an integrated health care system. Design: Retrospective study of patients with OCSCC (2007OCSCC ( -2010. Main Outcome Measures: Referral patterns and demographic, clinical, and tumor characteristics ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
10
1
2
Order By: Relevance
“…Access to health services, appointments, usage of public transportation, cultural and social backgrounds maybe additional explanations for a larger interval ( 5 , 7 ). Although some studies ( 8 , 24 - 26 ) report that patient interval is the most significant contributor to delay in the diagnosis, in our study both patient and professional compromised the total interval. Interestingly, some authors have described lower professional intervals in advanced malignancies that should be interpreted as a bias of urgent care and taken into account for future studies regarding the interval from diagnosis to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…Access to health services, appointments, usage of public transportation, cultural and social backgrounds maybe additional explanations for a larger interval ( 5 , 7 ). Although some studies ( 8 , 24 - 26 ) report that patient interval is the most significant contributor to delay in the diagnosis, in our study both patient and professional compromised the total interval. Interestingly, some authors have described lower professional intervals in advanced malignancies that should be interpreted as a bias of urgent care and taken into account for future studies regarding the interval from diagnosis to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…Diagnostic dilemmas have been identified in various areas of otolaryngology. In oral cavity cancer 21 and oropharyngeal squamous cell carcinoma, 19,20 diagnostic delays lead to poor outcomes and decreased survival. The dilemma is evident in chronic sinusitis, in which the symptoms overlap with other common conditions, including allergic rhinitis and viral upper respiratory tract infection 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 15 patients, 80% of patients who did not undergo aspirin desensitization required revision surgery 10 . Other studies in otolaryngology on oropharyngeal squamous cell carcinoma, 19,20 oral cavity cancer, 21 and laryngeal lesions 22 have also shown that diagnostic delay can lead to poor clinical outcomes. We aimed to describe a large cohort of AERD patients to further understand disease course, identify whether there is clinical diagnostic delay, and investigate whether diagnostic patterns contribute to clinical outcomes.…”
mentioning
confidence: 99%
“…Many types of oral lesions have malignant transformation potential, aptly named premalignant or precancerous lesions. Premalignant lesions are described by using clinical, pathological, histochemical, and also many other screening techniques for which lesions such as leukoplakia, lichen planus with oral and cutaneous form, erythroplakia, stomatitis nicotina, and submucous fibrosis are named or classified [3,10,15,18,22,[33][34][35]. In addition, there is less malign transformation potential in lesions such as discoid lupus erythematosus and also a lesser likelihood of malignant transformation in hereditary entities such as epidermolysis bullosa and dyskeratosis congenita [34].…”
Section: Look and See: Precancerous Mouth Lesionsmentioning
confidence: 99%